News and Analysis : Towards a fusion economy. (1st November 2019) - Chapman, Ian
Abstract: Ian Chapman, head of the Culham Centre for Fusion Energy (CCFE) in Oxfordshire, UK, talks to Michael Banks about how the lab is handling the uncertainty of Brexit and building for the future